Time and space resolved diagnostics for plasma thermal-chemical instability of fuel oxidation in nanosecond plasma discharges. (29th October 2020) - Rousso, Aric C; Goldberg, Benjamin M; Chen, Timothy Y; Wu, Shuqun; Dogariu, Arthur; Miles, Richard B; Kolemen, Egemen; Ju, Yiguang
Abstract: An instability in a nanosecond pulsed dielectric barrier discharge plasma occurring in methane–oxygen–argon mixtures is experimentally observed and measured by 1D time-resolved in situ electric field measurements. This instability, which seems to be created by the positive feedback between plasma kinetics and plasma-assisted low temperature fuel oxidation, is studied using electric field induced second harmonic generation and direct ICCD imaging. The rapid formation of streamers from an originally uniform discharge appears to be caused by the chemical kinetics of plasma-assisted low temperature methane oxidation, which may be resulting in a new type of plasma instability: a thermal-chemical instability. The results also revealed that the occurrence of this possible thermal-chemical instability in a reactive flow drastically changes the plasma properties by forming multiple secondary discharges and possibly leads to micron-sized non-uniform electric distributions. Single shot uncalibrated measurements of the electric field of the micron sized streamers appears to show much greater strengths than the average electric field. Furthermore, one-dimensional data analysis shows the positive feedback loop between the streamers and the low temperature plasma assisted oxidation chemistry in the plasma thermal-chemical instability. The present finding advances the understanding plasma instability growth and provides a new way to control plasma uniformity in plasma-assisted combustion and plasma fuel reforming.